The Alteration of Neonatal Raphe Neurons by Prenatal-Perinatal Nicotine: Meaning for Sudden Infant Death Syndrome - Eugenin-Leon, J; Llona-Rodriguez, I; Beltran-Castillo, S (American Thoracic Society, 2015)
Nicotine may link maternal cigarette smoking with respiratory dysfunctions in sudden infant death syndrome (SIDS). Prenatal-perinatal nicotine exposure blunts ventilatory responses to hypercapnia and reduces central respiratory chemoreception in mouse neonates at Postnatal Days 0 (P0) to P3. This suggests that raphe neurons, which are altered in SIDS and contribute to central respiratory chemoreception, may be affected by nicotine. We therefore investigated whether prenatal-perinatal nicotine exposure affects the activity, electrical properties, and chemosensitivity of raphe obscurus (ROb) neurons in mouse neonates. Osmotic minipumps, implanted subcutaneously in 5- to 7-day-pregnant CF1 mice, delivered nicotine bitartrate (60 mg kg-1 d-1) or saline (control) for up to 28 days. In neonates, ventilation was recorded by head-out plethysmography, c-Fos (neuronal activity marker), or serotonin autoreceptors (5HT1AR) were immunodetected using light microscopy, and patch-clamp recordings were made from raphe neurons in brainstem slices under normocarbia and hypercarbia. Prenatal-perinatal nicotine exposure decreased the hypercarbiainduced ventilatory responses at P1-P5, reduced both the number of c-Fos-positive ROb neurons during eucapnic normoxia at P1-P3 and their hypercapnia-induced recruitment at P3, increased 5HT1AR immunolabeling of ROb neurons at P3-P5, and reduced the spontaneous firing frequency of ROb neurons at P3 without affecting their CO2 sensitivity or their passive and active electrical properties. These findings reveal that prenatal-perinatal nicotine reduces the activity of neonatal ROb neurons, likely as a consequence of increased expression of 5HT1ARs. This hypoactivity may change the functional state of the respiratory neural network leading to breathing vulnerability and chemosensory failure as seen in SIDS. Copyright © 2015 by the American Thoracic Society.